2011
DOI: 10.1007/s10643-011-0474-9
|View full text |Cite
|
Sign up to set email alerts
|

Using a Teacher Rating Scale of Language and Literacy Skills with Preschool Children of English-Speaking, Spanish-Speaking, and Bilingual Backgrounds

Abstract: The purpose of this study was to examine the relationship between a teacher report measure, the Teacher Rating of Oral Language and Literacy (TROLL; Dickinson et al. in Teacher rating of oral language and literacy (TROLL): a research-based tool. Center for the Improvement of Early Reading Achievement, University of Michigan, Ann Arbor, 2001) and a direct behavioral measure of language development, the Preschool Language Scale-4 (PLS-4; Zimmerman et al. in Preschool Language Scale-4. The Psychological Corporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
5
1
1
Order By: Relevance
“…A method of screening that addresses several of the challenges associated with direct assessment is use of standardized checklists or rating scales, which are widely used to assess behavioral and emotional functioning of school‐aged children (Wilson & Reschly, ). Using rating scales for initial screening purposes might be ideal given that the forms can be completed at the rater's convenience, require no training to complete, are generally easy to score, and when developed appropriately, provide reliable and accurate information (Rodriguez & Guiberson, ). Given their experience working with children in their classroom for extended periods, teachers are in a prime position to detect and report on children's strengths and weaknesses (Pool & Hourcade, ).…”
Section: Importance Of Screeningmentioning
confidence: 99%
“…A method of screening that addresses several of the challenges associated with direct assessment is use of standardized checklists or rating scales, which are widely used to assess behavioral and emotional functioning of school‐aged children (Wilson & Reschly, ). Using rating scales for initial screening purposes might be ideal given that the forms can be completed at the rater's convenience, require no training to complete, are generally easy to score, and when developed appropriately, provide reliable and accurate information (Rodriguez & Guiberson, ). Given their experience working with children in their classroom for extended periods, teachers are in a prime position to detect and report on children's strengths and weaknesses (Pool & Hourcade, ).…”
Section: Importance Of Screeningmentioning
confidence: 99%
“…Based on survey data from Head Start teachers, Nungesser and Watkins (2005) suggested continuing need to educate teachers regarding the role of communication limitations and language based on teachers' misperceptions about the relationship between language and behavior in the classroom. Rodriguez and Guiberson (2011), who advocated teacher ratings of language, reported no significant correlation between a teacher report measure and a standardized language assessment for Spanish-speaking children. It is possible that the teacher perceptions of the child's language learning could be based on other behavioral variables not explored in this investigation.…”
Section: Correlation With Teacher Reportsmentioning
confidence: 99%
“…Lloyd, Kauffman, Landrum, and Roe (1991) reported that the majority of special education referrals are made by classroom teachers. Both teacher reports and classroom observations have been recommended as alternative assessment tools for use with ELLs (Damico, 1991;Rodriguez & Guiberson, 2011). While classroom observations are utilized in assessments and teacher reports are common referral sources, there is need for collaboration between professionals to establish reliability between observation, report and alternative assessment measures (Rodriguez & Guiberson, 2011;Tabors, 2008) Based on a functional perspective of language development and disorder, we would expect that a child with language deficits in morphology would also likely have deficits in learning elements of language that could be observed by teachers and also would be less likely to engage in social use of language in the classroom (Bates & MacWhinney, 1981;Owens, 2010).…”
Section: Classification Of Strong and Weak Language Learnersmentioning
confidence: 99%
“…. 본 연구에 서는 국외의 선행연구들 (Dickinson et al, 2001Gregory & Oetting, 2018;Rodríguez & Guiberson, 2011) The values presented at the diagonal were item-subscale Cronbach α. **p < .01.…”
mentioning
confidence: 99%
“…**p < .01. (Bradley & Bryant, 1983;Morais, 1991 (Bedore et al, 2011;Pua et al, 2017;Rodríguez & Guiberson, 2011), 이중언어 아동을 담당하고 있는 교사를 대상으로도 연 구를 확대하여 한국에서의 적용 가능성을 검증해 볼 필요가 있다.…”
unclassified